2019
DOI: 10.1002/cncr.32522
|View full text |Cite
|
Sign up to set email alerts
|

Site‐specific response patterns, pseudoprogression, and acquired resistance in patients with melanoma treated with ipilimumab combined with anti–PD‐1 therapy

Abstract: Background Patients with metastatic melanoma have variable responses to combination ipilimumab and nivolumab. The objectives of this study were to examine the patterns of response and survival in patients treated with combination ipilimumab and anti–PD‐1 therapy (IPI + PD1) and to explore the nature of pseudoprogression and acquired resistance. Methods Patients with metastatic melanoma who received treatment with first‐line IPI + PD1 had all metastases ≥5 mm measured on computed tomography/magnetic resonance i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
91
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 130 publications
(107 citation statements)
references
References 35 publications
(70 reference statements)
15
91
1
Order By: Relevance
“…The longitudinal analyses of multiple pre-treatment biopsies derived from various sites will be required to validate the influence of tumor heterogeneity on clinical outcomes and on the accuracy of baseline predictive signatures. In this study we observed significant variation in the response of individual lesions to immune checkpoint inhibition within melanoma patients, with heterogeneity of tumor responses observed in 85% and 69% of melanoma patients who did not achieve an objective response to pembrolizumab monotherapy or combination ipilimumab plus nivolumab, respectively 23,57 . This heterogeneity presumably reflects genetic, molecular and cellular variables, which may include the presence of neoantigens in only a subset of tumor clones, the expression of PD-L1 in a small proportion of tumor cells, variable expression of PD-1 on immune cells and intra-tumoral differences in T-cell density and clonality [58][59][60] .…”
Section: Discussionmentioning
confidence: 76%
“…The longitudinal analyses of multiple pre-treatment biopsies derived from various sites will be required to validate the influence of tumor heterogeneity on clinical outcomes and on the accuracy of baseline predictive signatures. In this study we observed significant variation in the response of individual lesions to immune checkpoint inhibition within melanoma patients, with heterogeneity of tumor responses observed in 85% and 69% of melanoma patients who did not achieve an objective response to pembrolizumab monotherapy or combination ipilimumab plus nivolumab, respectively 23,57 . This heterogeneity presumably reflects genetic, molecular and cellular variables, which may include the presence of neoantigens in only a subset of tumor clones, the expression of PD-L1 in a small proportion of tumor cells, variable expression of PD-1 on immune cells and intra-tumoral differences in T-cell density and clonality [58][59][60] .…”
Section: Discussionmentioning
confidence: 76%
“…In our cohort, patients with liver metastases had a significant worse rate of survival. The inferior outcome of patients with liver metastases treated by ICI has already been shown in other collectives, including patients treated with pembrolizumab and combined ipilimumab and nivolumab [42][43][44]. This might be due to a lower density of CD8 + T cells in the liver metastases and also in the distant non-liver metastases of these patients [42].…”
Section: Discussionmentioning
confidence: 84%
“…Our series show that specific metastatic sites are associated with better CPI response including neck lymph nodes (70%) and lung spread (58.6%), compared with unfavorable metastatic sites such as brain (7%) and bones (0%). Similarly, metastatic sites and survival association following CPI treatment, was lately demonstrated among advanced melanoma [24], renal cell carcinoma and non-small cell lung carcinoma [25] patients. Head and neck melanoma patients treated with CPI had a significantly better ORR (50%, p = 0.03) and an improved, durable, although non-significant, median overall survival of 60.2 months CI 95% [47.…”
Section: Plos Onementioning
confidence: 87%